Le discours d’un roi - Manon Brouillet (Cahiers Mondes Anciens)
Agamemnon’s excuses in book 19 of the Iliad have been considered very problematic for the understanding of action and its attribution to several agents in Homer. In this paper, I analyze how the king seeks to convince his audience by presenting his deeds as the result of a shared action, and then narrating a mythological story where Zeus seems to play the same part as himself. By focusing on the expression of agency, I show that the hero substitutes shared agency to responsibility for the evaluation of his action. Arguing that it is the result of the collaboration of the gods not only together but also with him, Agamemnon describes himself as an epic hero while, in the same time, assuming the part of the singer. In this text, the poet states that poetic utterance is needed for political reconciliation.